1996
DOI: 10.4039/ent128355-3
|View full text |Cite
|
Sign up to set email alerts
|

FORAGING BEHAVIOUR OF HONEY BEES (APIS MELLIFERAL.) ON STAGHORN SUMAC [RHUS HIRTASUDWORTH (EX-TYPHINAL.)]: DIFFERENCES AND DIOECY

Abstract: The Canadian Entomologist 128: 353-354 (1996) Detoxicative enzyme systems, such as the cytochrome P450 monooxygenases, gluthione S-hansferases, and general esterases, have been widely studied in holometabolous insects (e.g. Lepidoptera, Diptera, and Coleoptera). These, and other enzyme systems, play important roles in insecticide resistance, but are also important in insect-host plant relationships, because host range can partially depend on the ability of an insect to cope with putatively toxic allelochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
2
7
0
2
Order By: Relevance
“…For example honeybees which are collecting nectar prefer inflorescences of Lavandula stoechas with a high proportion of female flowers (which produce more nectar than male flowers), while individuals which are collecting both nectar and pollen choose inflorescences with a greater proportion of male flowers (Gonzalez et al 1995). Similar preferences for pollen or nectar producing flowers according to requirements have been recorded elsewhere, in honeybees (Kay 1982;Greco et al 1996), bumblebees (Alexander 1990;Cresswell & Robertson 1994) and solitary bees (Eckhart 1991). Clearly pollinators are able to distinguish between sexes or sexual phases of the flowers of at least some plant species, and are able to learn which provide the greatest reward.…”
Section: Flower Sexsupporting
confidence: 61%
“…For example honeybees which are collecting nectar prefer inflorescences of Lavandula stoechas with a high proportion of female flowers (which produce more nectar than male flowers), while individuals which are collecting both nectar and pollen choose inflorescences with a greater proportion of male flowers (Gonzalez et al 1995). Similar preferences for pollen or nectar producing flowers according to requirements have been recorded elsewhere, in honeybees (Kay 1982;Greco et al 1996), bumblebees (Alexander 1990;Cresswell & Robertson 1994) and solitary bees (Eckhart 1991). Clearly pollinators are able to distinguish between sexes or sexual phases of the flowers of at least some plant species, and are able to learn which provide the greatest reward.…”
Section: Flower Sexsupporting
confidence: 61%
“…Visits to female willow plants showed little diurnal variation with a more uniform, low‐level pattern throughout the day. Greco et al (1996), however, showed a pattern whereby Apis mellifera foraged on male staghorn sumac ( Rhus typhina ) during the morning but then switched to female flowers in the afternoon. Bumble bees ( Bombus spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of bee preferences on dioecious species can shift during the day and among days. Greco, Holland, and Kevan (1996), showed a pattern whereby Apis mellifera foraged on male staghorn sumac ( Rhus typhina ) during the morning but with a distinct shift to female flowers in the afternoon. Miliczky and Osgood (1995) observed differences in daily foraging activity between Andrena erythrogaster and A. nigrae on INT.…”
Section: Introductionmentioning
confidence: 99%
“…Die Art ist besonders bei Imkern beliebt (Greco et al 1996). Ältere Exemplare produzieren viele Samen, die allerdings einer ausgeprägten Keimhemmung unterliegen, die auch künstlich nur schwer zu überwinden ist.…”
Section: Verjüngungunclassified